Hypothyroidism as a Predictor of Surgical Outcomes in the Elderly - Vacante, Marco; Biondi, Antonio; Basile, Francesco; Ciuni, Roberto; Luca, Salvatore; Di Saverio, Salomone; Buscemi, Carola; Vicari, Enzo Saretto Dante; Borzì, Antonio Maria (Frontiers in Endocrinology, 2019)
There is a high prevalence of hypothyroidism in the elderly population, mainly among women. The most important cause is autoimmune thyroiditis, but also iodine deficiency, radioiodine ablation, and surgery may be responsible for hypothyroidism in elderly hospitalized patients. Thyroid-related symptoms are sometimes comparable to physiological manifestations of the aging process, and hypothyroidism may be related with many symptoms which can be present in critical patients, such as cognitive impairment, cardiovascular, gastrointestinal, and hematological alterations, and eventually myxedema coma which is a severe and life-threatening condition in older adults. Adequate thyroid hormone levels are required to achieve optimal outcomes from any kind of surgical intervention. However, only few randomized clinical trials investigated the association between non-thyroidal illness (or low-T3 syndrome), and adverse surgical outcomes, so far. The goal of this review is to discuss the role of thyroid function as a predictor of surgical outcomes in the elderly.